2014
DOI: 10.4236/ajps.2014.526395
|View full text |Cite
|
Sign up to set email alerts
|

Relative Competitiveness of Nimblewill (Muhlenbergia schreberi) with Tall Fescues and Kentucky Bluegrass

Abstract: Nimblewill (Muhlenbergia schreberi) is a warm-season perennial grass (weed) native to the United States and Canada with low palatability. This species is dominant in many horse pastures in which bluegrass (Poa pratensis) is the primary forage. Tall fescues infected with endophyte fungae gives tall fescue plants greater competitividade ability and enviromental stress tolerance than their noninfected counterparts. The purpose of this study was to compare the relative competitiveness of nimblewill with bluegrass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…In addition to sedges, dry woodland areas throughout the transition zone commonly host specimens of nimblewill (Muhlenbergia schreberi), a warm-season perennial grass traditionally regarded as a weed species in conventional turfgrass systems (de Moraes et al 2014a(de Moraes et al , 2014bFeatherly 1938).…”
mentioning
confidence: 99%
“…In addition to sedges, dry woodland areas throughout the transition zone commonly host specimens of nimblewill (Muhlenbergia schreberi), a warm-season perennial grass traditionally regarded as a weed species in conventional turfgrass systems (de Moraes et al 2014a(de Moraes et al , 2014bFeatherly 1938).…”
mentioning
confidence: 99%
“…内生真菌(fungal endophyte)是指在植物中度过 大部分或全部的生命周期但不使宿主植物表现明显 病症的一类真菌 (Arnold et al, 2000)。目前已知的感 染 禾 本 科 植 物 的 内 生 真 菌 共 有 7 个 属 , 分 别 是 Atkinsonella、Balansia、Balansiopsis、Echinodothis、 Epichloë、Myriogenospora和ParEpichloë (White & Reddy, 1998) lolii和Epichloë coenophiala构成共生关系 (Cheplick, 2004;Malinouski & Belesky, 2006;Leuchtmann et al, 2014)。已有研究表明: 内生真菌不仅可以促进宿主 植物的生长发育 (Clay, 1987), 而且能够提高宿主植 物 对 干 旱 (Elmi & West, 1995;Oberhofer et al, 2014)、食草动物取食 (Rudgers & Clay, 2008;Schardl et al, 2012)、病原菌危害 (Christensen, 1996;Xia et al, 2015) (Louis & Faeth, 1997;Schulthess & Faeth, 1998;Lewis, 2004) 或低磷 (Malinowski et al, 1999;周芳等, 2003)条件 下内生真菌感染才会促进宿主植物的生长。 内生真菌感染也能够影响宿主植物的竞争力。 以往的研究表明内生真菌感染不仅可以提高宿主植 物草甸羊茅(Festuca pratensis)、苇状羊茅、密丛雀 麦(Bromus benekeni)的种内竞争能力 (Marks et al, 1991;Malinowski et al, 1997;Brem & Leuchtmann, 2002), 而且也能够提高苇状羊茅、紫羊茅(Festuca rubra)的种间竞争能力 (Marks et al, 1991;Rudgers & Orr, 2009;Vázquez-de-Aldana et al, 2013)。当然, 内生真菌对宿主植物的竞争能力也存在负效应或无 影响 (Faeth et al, 2004;Moraes et al, 2014) (李学森等, 1998;Jones et al, 2000;Li et al, 2004), 而羽茅则不同, (Wei et al, 2006) (Collins & Foster, 2009): al., 1991;Rudgers & Orr, 2009) (Marks & Clay, 2007), 但也有少数研究认为 内生真菌在低氮生长条件下对宿主有利 (Arachavaleta et al, 1989;Cheplick et al, 1989;…”
unclassified
“…Other studies found that the presence of endophytes increased the ability of tall fescue and meadow fescue to compete with other plant species (Hoveland, Bouton, & Durham, 1999;Saikkonen et al, 2013). In contrast, some research has demonstrated conflicting results, showing neutral or negative effects of endophytes on the competitive ability of their hosts (Cheplick, Harrichandra, & Liu, 2014;Moraes, Witt, Phillips, Rossi, & Panozzo, 2014;Richmond et al, 2003).…”
mentioning
confidence: 99%